A novel lipids recovery strategy for biofuels generation on microalgae Chlorella cultivation with waste molasses - Yew, G.Y. (Elsevier Ltd, 2020)
This study demonstrated a novel approach of lipids extraction with simultaneous biofuels conversion on microalgae Chlorella sorokiniana CY-1 cultivation using waste molasses as culture medium. The lipid extraction process was based on a hybrid liquid biphasic system (HLBS) which comprises of disruptive and extractive solvents in a single system. The microalgae cultivation with waste molasses showed a reduction in the chemical oxygen demand (COD), total suspended solid (TSS) and nitrate content on the waste medium (61.48 , 63.94 and 63.79 , respectively). Additionally, a prompt lipids extraction with a recovery of 92.84 and a cell disruption enhancement of 8.3-fold in the organic solvent phase was attained. The acid-treated C. sorokiniana CY-1 biomass showed a composition of carbon at 61.3 , oxygen at 33.2 , nitrogen at 5.5 and potassium at 0.12 . Sulphur content was not detected in the microalgae biomass and this had aided the production of fatty acids methyl ester (FAME) which was observed by a gas chromatographic-flame ionisation detector (GC-FID) profile. A disruptive-extraction method using acid assisted phase on HLBS showed potential for direct conversion of lipids into FAME to produce biofuels for engine combustion. Â© 2020 Elsevier Ltd